REVIEWING CHALLENGES OF CURRICULUM IMPLEMENTATION IN CAMBODIAN TEACHER EDUCATION AND POSSIBILITIES FOR IMPROVEMENT - Run, Netra; Tep, Phirun; Mot, Narin; Phuong, Chanleaphy (jfpublisher, 2025)
Since the challenges in curriculum development in the Cambodian context were unclear and scattered, its collections would be a priority to see a whole image of challenges along with possible solutions for the developer, practitioner, and stakeholders. This paper aims to review the challenges of curriculum implementation in Cambodian teacher education and the possibilities for improvement. The integrative review approach of the conventional review paper was employed to form a new framework of selective secondary sources. 18 articles (16 primary and 2 secondary data) were collected from Google Scholar under 4 criteria: (1) content-related paper, (2) no longer than 10 years of publication, (3) primary or secondary data, and (4) ASEAN reflection on the Cambodian context. The findings indicated five main challenges of curriculum implementation in Cambodian Teacher Education: (1) teaching and learning activities, (2) instructional materials, (3) assessment, (4) teacher career pathway, and (5) external factors. The possibilities for improvement to overcome these challenges also involved five main solutions for improvement as mentioned above, along with three elements that were hidden such as (1) system, (2) practices, and (3) production. The course designers and key practitioners may put theories into practice by gathering information, reflecting, and making possible changes in curriculum implementation for notation and improvement.